(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
Dimensions of Entrepreneurship (Patenting Licensing-PL, Contract Research-CR, Consulting-C, Science Parks-SP), work to achieve the goals of Industrial Organizations (IO) and provide continuous training to raise their efficiency. The entrepreneurship dimensions in industrial organizations, and here the researcher uses the quantitative method. Sample 85 the Iraqi National Oil Company. There were 80 valid questionnaires and 5 missing questionnaires. The researcher focused on SPSS to obtain the results. The results reached between the dimensions of entrepreneurship and industrial organizations are supportive and consist of four theories. The four positive hypotheses have proven effective in developing industrial organizations in the Iraqi National Oil Company